PERAN DAN FUNGSI KEPALA MADRASAH DALAM MENINGKATKAN PROFESIONALISME GURU - Ismail Anas (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
The role of madrasah principals in improving teacher professionalism is critical for addressing the inherent complexity and uniqueness of educational organizations. As managers, leaders, and educators, principals must integrate strategic oversight, inspirational leadership, and educational guidance to foster a conducive teaching and learning environment. This study examines how principals optimize resources, inspire commitment among educators, and embed moral and intellectual values within the teaching framework. By critically analyzing the managerial, leadership, and educational dimensions, this research highlights the gaps between existing practices and the ideal competencies required for achieving systemic improvements in teacher professionalism. The findings underscore the importance of adopting adaptive strategies, evidence-based decision-making, and a vision-oriented approach to leadership, ensuring that madrasahs effectively respond to both internal challenges and external educational demands. This analysis contributes to the discourse on transformative leadership in Islamic education and its pivotal role in enhancing teacher performance and organizational success.